AGNIQUE AMD 3L as green solvent for polyethersulfone ultrafiltration membrane preparation. Issue 9 (23rd August 2019) - Gronwald, Oliver; Weber, Martin
ABSTRACT: With the advent of the green chemistry concept novel, innocuous, biodegradable solvents require introduction in industrial processes. N, N ‐dimethyl lactamide (AGNIQUE AMD 3L) represents a bio‐based, biodegradable, label‐free polar, protic solvent. In this article, AGNIQUE AMD 3L is introduced as novel solvent for preparation of polyethersulfone (PESU) nonsolvent‐induced phase separation ultrafiltration membranes using polyvinylpyrrolidone or poly(ethylene oxide) as second dope additives. Analysis of Hansen solubility parameters indicates good solvent–polymer interactions for polymer dope compositions required for PESU membrane manufacturing. Depending on the process conditions, PESU ultrafiltration membranes with hydraulic permeability values up to 610 kg m −2 × bar × h and molecular weight cutoff value of 20 kDa were obtained. Scanning electron microscope of membrane cross sections reveals perfect defect‐free, asymmetric morphologies. As a result, AGNIQUE AMD 3L provides a new alternative as replacement for polar, aprotic solvents employed in membrane manufacturing so far. © 2019 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2020, 137, 48419. Abstract : Agnique AMD 3L as green solvent for ultrafiltration membrane preparation.